(untitled) (Journal of the College of Basic Education, 2022)
Two field experiments were conducted during the summer season 2013 in the Botanical Garden of the Department of Life Sciences, College of Education for Pure Sciences/Ibn Al-Haytham/University of Baghdad, with the aim of studying the effect of drought stress and spraying with aspirin and the interaction between them on some morphological characters of two sunflower cultivars Helianthus annuus L., and the coefficients were Drought stress is irrigation every seven days, irrigation every 14 days, while the concentrations of aspirin were 0, 50, 100 ppm.